Perspectives on distance education : foreign providers in the Caribbean : pillagers of preceptors? - Marshall, Stewart...[et al.] (Commonwealth of Learning VancouverCA, 2008)
Examines some of the issues and perspectives on the presence of external providers in the tertiary landscape of the Caribbean.